Memikirkan Kembali Misi Trinitaris : Perspektif Lesslie Newbigin Dan Johan Herman Bavinck - Doni Herwanto Harianja; Antonius S. Un (VERBUM CHRISTI JURNAL TEOLOGI REFORMED INJILI, 2020)
This article is an overview of the ideas of Lesslie Newbigin and Johan Herman Bavinck in thinking about the basis of the Trinity on a theology of mission. These two missionaries agreed to base their mission on the doctrine of the Trinity. The mission-based on the doctrine of Trinity is the mission that does not distinguish between the gospel and social justice or "Word" and "deed". There are various reasons and aspects put forward by Newbigin and Bavinck for the importance of the doctrine of the Trinity for the mission. These two figures have something in common. They believe that missions based on the Trinity framework can answer challenges and obstacles in the mission field. When reviewing the differences between these two figures, Newbigin concluded that a proper theological foundation of the mission is based on the Triune God build upon one's struggles in mission service and participation in the IMC-WCC organization. As for Bavinck, it is essential to investigate the Bible first to conclude that mission is based on the Triune God.